Sun & Spoon - Henkes, Kevin (New York : Puffin Books, 1998)
After the death of his grandmother, ten-year-old Spoon tries to find the perfect artifact to preserve his memories of her.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
5.8
3-6
Keywords: Death -- Fiction; Grandmothers -- Fiction; Grief -- Fiction; Death -- Fiction; Grandmothers -- Fiction; Grief -- Fiction